2020
DOI: 10.5194/wes-5-997-2020
|View full text |Cite
|
Sign up to set email alerts
|

Validation of uncertainty reduction by using multiple transfer locations for WRF–CFD coupling in numerical wind energy assessments

Abstract: Abstract. This paper describes a method for reducing the uncertainty associated with utilizing fully numerical models for wind resource assessment in the early stages of project development. The presented method is based on a combination of numerical weather predictions (NWPs) and microscale downscaling using computational fluid dynamics (CFD) to predict the local wind resource. Numerical modelling is (at least) 2 orders of magnitude less expensive and time consuming compared to conventional measurements. As a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The WRF was chosen as the appropriate model since it has been extensively validated over the years and constitutes one of the most robust and reliable NWP models [50][51][52][53][54]. In recent years, attempts to utilise the WRF, coupled with or without CFD models, for the study of wind potential can be found in the literature [55][56][57][58][59][60][61]. However, none of these works have attempted to go below 500 m spatial resolution and, to the best of our knowledge, no research has attempted to utilise and test the validity of the "10% sampling condition" for the study of wind potential.…”
Section: Nwp Model Predictionsmentioning
confidence: 99%
“…The WRF was chosen as the appropriate model since it has been extensively validated over the years and constitutes one of the most robust and reliable NWP models [50][51][52][53][54]. In recent years, attempts to utilise the WRF, coupled with or without CFD models, for the study of wind potential can be found in the literature [55][56][57][58][59][60][61]. However, none of these works have attempted to go below 500 m spatial resolution and, to the best of our knowledge, no research has attempted to utilise and test the validity of the "10% sampling condition" for the study of wind potential.…”
Section: Nwp Model Predictionsmentioning
confidence: 99%